Breathing, feeding, and neuroprotection - Homma, I. (Springer, 2006)
New findings in brain research are being revealed on an almost daily basis, and the focus of this book is the fields of breathing, neuroprotection, and higher brain functions. An unresolved issue within respiration research and hence a topic of much interest is Where and how respiratory rhythm is generated in the brainstem, detailed analysis of which is presented herein. Chapters on neuroprotection examine the functional significance of the blood – brain barrier as an interface of blood and the central nervous system; other chapters look at health and disease in relation to the hypothalamic and limbic systems. In addition to animal experiments, research on the human brain is included, with a focus on the recently developed EEG/dipole tracing method. This book will be an invaluable reference for researchers in neuroscience and related fields. Centra regulation of breathing -- Visualization of respiratory neuron activity in the ventral medulla from a newborn rodent -- Search for genes involved central respiratory failure using mice models -- Control of central histaminergic neurons for respiration during hypercapnia in conscious mice -- Neurogeneration and neuroprotection -- The role of the blood-brain barrier in feeding: leptin -- Ultrastructural study on the demyelination of the white matter in the rat spinal cord after cardiac arrest and massive hemorrhagic shock -- Engagement of proinflammatory cytokines after cerebral ischemia -- Levels of the alkoxy radical in patients with brain death -- Differentiation of neural stem cells into astrocytes by low concentration of pituitary adenylate cyclase-activating polypeptide (PACAP) -- Neurogenesis is toxicologically heterogeneous: a case of BrdU-induced cell death -- Brain functions in health and disease -- Hypocretin-deficient narcolepsy as a disease model to study the hypothalamic function in health and disease -- The expression of synaptic vesicle proteins after chronic antidepressant treatment in rat brain -- Identification of molecular systems responsible for the therapeutic effect of antidepressant -- S-100B expression in neonatal rat cortical “Barrels” and thalamic “Barreloids” -- Postnatal change of glycinergic synaptic transmission from supratrigeminal region to trigeminal motoneurons -- Central nervous system concerned with the stress induced inhibition of cellular immune activity -- Brain functions by the dipole tracing method -- Can not live without breathing, without emotions -- Breathing mind in ‘Noh’ -- The source generator of event-related potentials with recognizing facial expression by the dipole tracing method -- Source localization of event-related potentials related to cross-modal semantic interference effect using scalp-skull-brain dipole tracing method.